Echoes of Mercy - Bassey, Edward (Literamed Publications Nigeria Ltd, 2003)
Echoes of Mercy is a well-narrated story of a young man, Ene with an abundance of potentials sufficient to weather the storm of life. But in spite of his hard work, determination and perseverance, fortune refuses to smile on him. He is at the verge of losing his life when the light of mercy shines on him and turns around his life for good.
Keywords: Fiction; Juvenile Literature